Emergence and Spread of Enterobacterales with Multiple Carbapenemases after COVID-19 Pandemic - Branka Bedenić; Josefa Luxner; Haris Car; Sanda Sardelić; Maja Bogdan; Dijana Varda-Brkić; Sandra Šuto; Andrea Grisold; Nataša Beader; Gernot Zarfel (Pathogens, 2023)
Resistance to carbapenems in Enterobacterales has become a matter of the highest concern in the last decade. Recently, Enterobacterales harboring multiple carbapenemases were detected in three hospital centers in Croatia and in the outpatient setting, posing a serious therapeutic challenge for clinicians. In this study, we analyzed eight Klebsiella pneumoniae and two Enterobacter cloacae complex isolates with multiple carbapenemases, with regard to antibiotic susceptibility, β-lactamase production and plasmid content. The isolates demonstrated uniform resistance to amoxicillin/clavulanate, piperacillin/tazobactam, cefuroxime, ceftazidime, cefotaxime, ceftriaxone and ertapenem. Among novel β-lactam/inhibitor combinations, ceftazidime/avibactam exhibited moderate activity, with 50% of isolates susceptible. All isolates demonstrated resistance to imipenem/cilastatin/relebactam, and all but one to ceftolozane/tazobactam. Four isolates exhibited a multidrug-resistant phenotype (MDR), whereas six were allocated to an extensively drug-resistant phenotype (XDR). OKNV detected three combinations of carbapenemases: OXA-48+NDM (five isolates), OXA-48+VIM (three isolates) and OXA-48+KPC (two isolates). Inter-array testing identified a wide variety of resistance genes for β-lactam antibiotics: blaCTX-M-15, blaTEM, blaSHV, blaOXA-1, blaOXA-2, blaOXA-9, aminoglycosides: aac6, aad, rmt, arm and aph, fluoroquinolones: qnrA, qnrB and qnrS, sulphonamides: sul1 and sul2 and trimethoprim: dfrA5, dfrA7, dfrA14, dfrA17 and dfrA19. mcr genes were reported for the first time in Croatia. This study demonstrated the ability of K. pneumoniae and E. cloacae to acquire various resistance determinants under the selection pressure of antibiotics widely used during the COVID-19 pandemic. The novel inter-array method showed good correlation with OKNV and PCR, although some discrepancies were found.